Africa RISING-Soybean Baby Trial in Northern Ghana - International Institute of Tropical Agriculture; Ministry of Food and Agriculture, Government of Ghana; Savanna Agricultural Research Institute (International Food Policy Research Institute, 2015)
This data study contains three-year data from three northern regions of Ghana which were collected to evaluate and demonstrate soybean practices.